Synodal Structures in the Syro-Malabar Church with Special Focus on Palliyogam - Maniyattu, Pauly (Asian Horizons, 2025)
This article examines the various ecclesial structures of the Syro-Malabar Church which contribute to the synodality of the Church. The Syro-Malabar Church of the St Thomas Christians maintained the principle of synodality in the various aspects of the ecclesial life. Mar Thoma Margam, the very name given to the sum total of the ecclesial existence of St Thomas Christians, points to the synodal character of this ecclesial tradition. In the tradition of St Thomas Christians, the synodality of the bishop was realized to a great extent through the ministry of Archdeacon and Corepiscopa, who were priests with the extra orders of Archdeacon and Corepiscopa. Archdeacon as the ‘Jathikku Karthavyan,’ took care of the administration of the Church, for which he was helped by the Pothuyogam, the General Assembly of the Church. Another important element that contributed to the synodality of St Thomas Christians was the Yogam (assembly) of various levels: Pothuyogam (General Assembly), Pradesikayogam (Regional Assembly), and Palliyogam (Parish Assembly). Palliyogam had a great say in the day-to-day administration of the parish Church. However, it is unfortunate that today the ecclesiastical Yogams do not have the same power which they enjoyed in the past. In the modern times the synodality of the Church is manifested to a great extent through the Synod of Bishops of a Patriarchal or Major Archiepiscopal Church.